2011
DOI: 10.1007/s10344-011-0553-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the status of wild deer as hosts of Mycobacterium bovis infection in Britain

Abstract: Control of livestock diseases can become complicated when wild animals are involved. The Eurasian badger (Meles meles) is considered the principle wildlife host of Mycobacterium bovis (which causes bovine tuberculosis, bTB) in Great Britain and Ireland, but wild deer have also been implicated. Whether wild deer are likely to perpetuate bTB in cattle depends on the exposure risks they pose, the mode of pathogen transmission, the distances over which the disease can be transported and whether they can maintain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Three scenarios of theoretical probability of infection were considered: 0.1, 0.2 and 0.5. The probability of infection given interaction in wild conditions is a difficult parameter to estimate, so we selected these values according to a range of β parameter presented in previous works, which modeled the transmission of a pathogen transmitted through direct pathways (foot and mouth disease [FMD]; [58,59]) and indirect pathways (animal tuberculosis [TB]; [60]). These are two relevant infectious diseases in Spain since, although this country has been FMD free since 1986, there is a real risk of pathogen introduction through animal imports [61].…”
Section: Simulation Of Pathogen Transmissionmentioning
confidence: 99%
“…Three scenarios of theoretical probability of infection were considered: 0.1, 0.2 and 0.5. The probability of infection given interaction in wild conditions is a difficult parameter to estimate, so we selected these values according to a range of β parameter presented in previous works, which modeled the transmission of a pathogen transmitted through direct pathways (foot and mouth disease [FMD]; [58,59]) and indirect pathways (animal tuberculosis [TB]; [60]). These are two relevant infectious diseases in Spain since, although this country has been FMD free since 1986, there is a real risk of pathogen introduction through animal imports [61].…”
Section: Simulation Of Pathogen Transmissionmentioning
confidence: 99%
“…Reports published over the past decade or so suggest that most of these populations have been steadily growing (Battersby, ; Mathews et al, ; Ward, ). In large numbers, deer can inflict substantial damage to woodland and crops (Putman & Moore, ) as well as providing a reservoir for the transmission of diseases, some of which can affect livestock and human health, for example, bovine tuberculosis (Ward & Smith, ) and foot‐and‐mouth disease (Böhm, White, Chambers, Smith, & Hutchings, ). In contrast, their populations may be threatened by the introduction of novel diseases, such as chronic wasting disease (Ricci et al, ) which has severely impacted some cervid species in the USA (Monello et al, ) and has recently been reported in Europe (Benestad, Mitchell, Simmons, Ytrehus, & Vikøren, ).…”
Section: Introductionmentioning
confidence: 99%
“…Where these external sources of infection include maintenance hosts, disease control strategies should include management of these other potential sources of disease. However, effective control of bTB in the badger population may also help to reduce the significance of these external sources, especially if the other species are acting solely as spillover hosts [ 32 ]. With larger group sizes, even occasional infectious disease contact can cause low levels of disease to persist, thereby complicating control measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, only some of the affected species excrete bTB and are therefore capable of contributing to a pool of external infection. Of the affected species, only fallow deer and muntjac, at densities of over 56 per km 2 and 47 per km 2 respectively, are likely to act as maintenance hosts [ 32 ]. Spillover host status may be provided by roe deer, red deer, muntjac and fallow deer at lower densities [ 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation